Keterampilan Literasi Pemustaka dalam Memanfaatkan Sumber Informasi di Perpustakaan Universitas Bosowa - Hermawan, Nanang; Rahman, Idzhari; Arif, Arnawan (Literatify: Trends in Library Developments, 2026)
The purpose of this study is to evaluate the ability of library users in using information sources available at the Bosowa University Library. Librarians at the Bosowa University Library assist library users to support improving their literacy skills in meeting their information needs. This study uses a descriptive qualitative approach to understand library users' literacy behavior through observation, in-depth interviews, and documentation. The results of the study indicate that library users at the Bosowa University Library have sufficient literacy skills to browse and utilize digital and printed materials. To meet their academic information needs, most users utilize online catalogs, e-journals, and print collections.